(untitled) (Panauti Journal, 2025)
Agricultural extension plays a crucial role in enhancing productivity and livelihoods, and its effectiveness in Nepal is increasingly shaped by the country’s transition to a federal governance system. This paper assesses institutional reforms for strengthening agricultural extension under federal governance in Nepal. This study used a library method for exploring decentralized policies and programs as well as devolved power/jurisdictions to the local government. The study found that the timeline of extension development shows a gradual change in historical context following the adoption of the federal system. Key features of federalization include expanded farmer engagement, improved access to resources, and the capacity to customize policies to local requirements. Federalization has provided the opportunity for farmers’ participation and a bottom-up approach for planning agricultural extension programs. However, obstacles exist, such as institutional inefficiencies, unclear power structures, and scarcity of human resources at the local level. This paper highlights the importance of increased institutional capacity of the local government. Therefore, the government must strengthen local capacity through training and technology, foster multi-stakeholder coordination, and implement participatory, evidence-based planning to ensure effective, inclusive, and sustainable agricultural extension services in a federal context.